Resting-State Functional MRI/PET Profile as a Potential Alternative to Tri-Modality EEG-MR/PET Imaging: An Exploratory Study in Drug-Refractory Epilepsy - Mangalore, Sandhya; Peer, Sameer; Khokhar, Sunil Kumar; Bharath, Rose Dawn; Kulanthaivelu, Karthik; Saini, Jitender; Sinha, Sanjib; Kishore, Vyasaraj Kalya; Mundlamuri, Ravindranadh Chowdary; Asranna, Ajay; Lakshminarayanapuram Gopal, Vishwanath; Kenchaiah, Raghavendra; Arimappamagan, Arivazhagan; Sadashiva, Nishanth; Rao, Malla Bhaskara; Mahadevan, Anita; Rajeswaran, Jamuna; Kumar, Keshav; Thennarasu, Kandavel (Asian Journal of Neurosurgery, 2023)
Objective The study explores whether the epileptic networks associate with predetermined seizure onset zone (SOZ) identified from other modalities such as electroencephalogram/video electroencephalogram/structural MRI (EEG/VEEG/sMRI) and with the degree of resting-state functional MRI/positron emission tomography (RS-fMRI/PET) coupling. Here, we have analyzed the subgroup of patients who reported having a seizure on the day of scan as postictal cases and compared the findings with interictal cases (seizure-free interval).Methods We performed independent component analysis (ICA) on RS-fMRI and 20 ICA were hand-labeled as large scale, noise, downstream, and epilepsy networks (Epinets) based on their profile in spatial, time series, and power spectrum domains. We had a total of 43 cases, with 4 cases in the postictal group (100%). Of 39 cases, 14 cases did not yield any Epinet and 25 cases (61%) were analyzed for the final study. The analysis was done patient-wise and correlated with predetermined SOZ.Results The yield of finding Epinets on RS-fMRI is more during the postictal period than in the interictal period, although PET and RS-fMRI spatial, time series, and power spectral patterns were similar in both these subgroups. Overlaps between large-scale and downstream networks were noted, indicating that epilepsy propagation can involve large-scale cognition networks. Lateralization to SOZ was noted as blood oxygen level–dependent activation and correlated with sMRI/PET findings. Postoperative surgical failure cases showed residual Epinet profile.Conclusion RS-fMRI may be a viable option for trimodality imaging to obtain simultaneous physiological information at the functional network and metabolic level.
Keywords: epilepsy; epileptic network; resting-state functional MRI; fluorodeoxyglucose; positron emission tomography; temporal lobe epilepsy